Social Identification in Multiteam Systems: The Role of Depletion and Task Complexity - Porck, Jeanine P.; Matta, Fadel K.; Hollenbeck, John R.; Oh, Jo K.; Lanaj, Klodiana; Lee, Stephanie M. (Academy of Management Journal, 2019)
Organizations construct multiteam systems to address complex challenges that require the joint efforts of multiple teams. Taking an uncertainty perspective and integrating social identity theory with depletion research, we theoretically and empirically examine the role of social identification in multiteam system performance. In contrast to general assumptions in the literature regarding the need to develop identity at the highest level of a system, we argue that within a multiteam system, identification with that system negatively relates to multiteam system performance, whereas identification with the component team positively relates to multiteam system performance. Our uncertainty perspective suggests that identification with the multiteam system introduces uncertainty regarding the appropriate norms and interdependencies in the system, which leads to more depletion, and consequently lower system performance. Conversely, identification with the component team offers less uncertainty, resulting in less depletion and higher multiteam system performance. Thus, our integrated theoretical framework suggests that depletion mediates the negative effects of multiteam system identification and the positive effects of component team identification on multiteam system performance. Moreover, consistent with our uncertainty perspective, the indirect effect of identification on multiteam system performance via depletion is stronger when task complexity is high and weaker when task complexity is low.